2020
DOI: 10.1021/acs.jpcc.0c08494
|View full text |Cite
|
Sign up to set email alerts
|

Universal Intrinsic Dynamics and Freezing of Water in Small Nanotubes

Abstract: Although it is well known that confinement alters the freezing point of water, the mechanism by which this occurs, particularly in small nanotubes, is still under active research. It was recently claimed [Agrawal et al. Nat. Nanotechnol. 12, 2017, 267] that the freezing point of water in a carbon nanotube of a certain size may be as high as its boiling point under bulk conditions or even higher. A more recent paper [Chiashi et al. ACS Nano. 13, 2019, 1177 reported that the change in the freezing point may no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Does the tube shape affect the formation of square ice? Computer simulations demonstrate that this ice is formed in cylindrical CNTs, 23 silicon carbide nanotubes, 53 and irregularly shaped cylindrical channels of AFI-type PSZ. 54 These investigations show that ice formation has a general character and that the type of ice depends on the width of the pore and, to a small extent, on the chemistry or pore shape.…”
Section: Resultsmentioning
confidence: 96%
“…Does the tube shape affect the formation of square ice? Computer simulations demonstrate that this ice is formed in cylindrical CNTs, 23 silicon carbide nanotubes, 53 and irregularly shaped cylindrical channels of AFI-type PSZ. 54 These investigations show that ice formation has a general character and that the type of ice depends on the width of the pore and, to a small extent, on the chemistry or pore shape.…”
Section: Resultsmentioning
confidence: 96%
“…It is known that the sharp decrease in the peak of the radial distribution function is a sign of phase transition [ 35 ]. To quantify the possible transition temperature, we computed radial distribution functions of water molecules confined inside the CNT, which are defined as: where N is the total number of water molecules and is the distance between the i th and j th molecules along the x–y axis.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Koḧler et al 35 have performed MD simulations to reveal that water molecules confined in different MoS 2 nanotubes display distinct structural transitions from singlefile to pentagonal ice to bulk-like patterns due to the variation of the HB network as the nanotube diameter. Sahimi and coworkers 41 further verified that weakened HBs should be responsible for the depression of the freezing by comparing the formation of HB networks in CNT and silicon-based nanotube. Besides the structures in 1-D nanoconfinement, the milestone MD work of Hummer et al 31 revealed that single-file water chain in (6,6) CNT has a pulselike diffusion pattern via bursts of their HB network (denoted as the singlefile diffusion) and yield an extraordinary flow speed of around 51 × 10 −14 cm 3 s −1 .…”
Section: ■ Introductionmentioning
confidence: 92%
“…One-dimensional (1-D) materials, such as carbon nanotube (CNT), MoS 2 nanotube, silicon-based nanotube, and other nanotubes, have been researched as host materials to explore the nanoconfined behavior of water molecules, including structures, dynamics, and their relationships with the HB properties. For example, earlier MD simulations of Wang et al revealed that single-file water chains can be formed only in narrow CNTs with a diameter of 0.676–0.811 nm and the helicity of CNT rarely affects the structural properties.…”
Section: Introductionmentioning
confidence: 99%